Color-based Image Retrieval Using Wavelet. - Sumari, Putra; Haili, Hailiza Kamarul; Budiarto, Rahmat (2004)
There has been a great demand for efficient systems that can rapidly retrieve images of interest from a large quantity of images on the basis of the pictorial content such as color.